Pengembangan Media Busy Book untuk Meningkatkan Literasi Lingkungan pada Mata Pelajaran IPA Kelas V - Rahmawati Iswantary; Donna Boedi Maritasari; Abdul Aziz; Aswasulasikin Aswasulasikin (STKIP Melawi, 2023)
Abstract: This study aims to develop learning media in the form of Busy Books to improve students' environmental literacy in science subjects for class V. This study uses the ADDIE development model that has been developed by Robert Maribe Branch, which consists of five steps, namely analysis, design, development, implementation, evaluation. The results of media validation get results in the